1977
DOI: 10.1590/s0373-55241977000200003
|View full text |Cite
|
Sign up to set email alerts
|

Note on the occurrence of saline fronts in the Ilha Grande (RJ) region

Abstract: Continuous records of temperature and salinity were obtained on the surface waters as function of the horizontal distances around Ilha Grande region, on June 21, 1975; an outflow of less saline (S~33.10º /oo ) and slightly warmer water was detected throughout the region between Ponta de Castelhanos and Ponta Grossa da Marambaia and a visible manifestation of a saline front was observed in the interaction of this outflow with the coastal and more saline water (S~ 35.4 to 35.6º /oo). The recorded salinity values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The ratios 206 Pb/ 207 Pb for the Paraty Bay had shown a variation between 1.180 and 1.202 and can be compared to reported anthropogenic signatures in other studies in Brazil. The isotopic signatures of the Pouso Bay indicate [9]. The comparison of these values with data of the literature of studies in coastal areas in Brazil is shown in Figure 7.…”
Section: Discussionmentioning
confidence: 59%
“…The ratios 206 Pb/ 207 Pb for the Paraty Bay had shown a variation between 1.180 and 1.202 and can be compared to reported anthropogenic signatures in other studies in Brazil. The isotopic signatures of the Pouso Bay indicate [9]. The comparison of these values with data of the literature of studies in coastal areas in Brazil is shown in Figure 7.…”
Section: Discussionmentioning
confidence: 59%
“…The significance of flows related to various forces has been widely acknowledged in studies, including factors such as local wind friction and density [32][33][34]. However, as noted by Kjerfve et al [35], for the Ilha Grande Channel, wind and ocean dynamics take on a paramount role in local hydrodynamics, accounting for 67% of the annual variation in sea levels.…”
Section: Introductionmentioning
confidence: 99%